Expression of Bordetella pertussis Antigens Fused to Different Vectors and Their Effectiveness as Vaccines - Han Xu; Jing Huang; Zhaolu Liu; Xin Li; Kangfeng Wang; Erling Feng; Jun Wu; Li Zhu; Kaihu Yao; Chao Pan; Hengliang Wang (Vaccines, 2021)
Pertussis is an acute respiratory tract infection caused by Bordetella pertussis. Even though its current vaccine coverage is relatively broad, they still have some shortcomings such as short protection time and might be incapable of blocking the spread of the disease. In this study, we developed new pertussis vaccine candidates by separately fusing three pertussis antigens (B. pertussis fimbriae 2 “Fim2”, pertussis toxin S1 subunit “PtxS1”, and filamentous hemagglutinin “FHA1877–2250”) to each of two immune-boosting carrier proteins (B subunits of AB5 toxin family: cholera toxin B subunit “CTB” and shiga toxin B subunit “StxB”). We then immunized mice with these fusion antigens and found that they significantly increased the serum antibody titers and elicited high bactericidal activity against B. pertussis. After CTB-or StxB-fused antigen-immunized mice were challenged with a non-lethal dose of B. pertussis, the bacterial loads in different tissues of these mice were significantly reduced, and their lung damage was nearly invisible. Furthermore, we also demonstrated that these candidate vaccines could provide strong prophylactic effects against a lethal challenge with B. pertussis. Overall, our candidate vaccines conferred better immune protection to mice compared with pertussis antigen alone. This B5 subunit-based vaccine strategy provides a promising option for vaccine design.